DDDR-29. THE HYDROGEL-CXCL9-MRNA (HCM) VACCINE RESULTS IN SIGNIFICANT ANTI-TUMOR EFFICACY THROUGH RECRUITMENT OF NATURAL KILLER (NK) CELLS. (14th November 2022) - Dastmalchi, Farhad; Thomas, Nagheme; Ebrahim, Ghaidaa; Frain, Matt; Moore, Ginger; Mendez-Gomez, Hector; Sayour, Elias; Tomdio, Macaulay; Subramaniam, Vignesh; Angelini, Thomas; Mitchell, Duane; Rahman, Maryam
Abstract: INTRODUCTION: Immunotherapy for GBM has resulted in limited benefits to overall survival due to the targeting of limited antigens and the hostile TME. Our group has developed a patented vaccine platform that combines an mRNA-nanoparticle with CXCL9 loaded polyethylene glycol (PEG) hydrogel. The HCM vaccine is given SQ and recruits a diverse immune cell population to deliver a large payload of mRNA. The objective of these studies was to evaluate the efficacy and mechanisms of action of the HCM vaccine. METHODS: C57BL/6 mice underwent intracranial implantation of KR158 glioma cells. The HCM vaccine was formulated with total tumor mRNA, DOTAP, CXCL9 and PEG hydrogel created in collaboration with the College of Engineering. Survival studies were analyzed with the Mantel-Cox test. Flow cytometry and ELISA data was analyzed using ANOVA. Graphpad was used for statistical analysis. RESULTS: KR158-glioma intracranial tumor bearing mice were treated with SQ injection of the HCM vaccine (total tumor mRNA, DOTAP, CXCL9, PEG hydrogel). KR158 tumor bearing animals are resistant to treatment with radiation, temozolomide and other immunotherapy platforms in our laboratory. Treatment animals lived significantly longer compared to control animals (35 days versus 22 days, p < 0.0001). In a separate experiment, the fat pad was collected after vaccination and flow cytometry revealed recruitment of dendritic cells (DCs), CD4 and CD8 T cells and NK cells. Large numbers of antigen specific CD8 T cells were found in the spleen and within the TME after vaccination. When NK cells were blocked (NK 1.1 blocking antibody), the survival benefit from the vaccine was completely abrogated. NK cells were found to increase antigen presentation and available IFN-gamma within the PEG hydrogel scaffold. CONCLUSION: The HCM vaccine demonstrates efficacy in resistant murine glioma models and the efficacy is dependent on recruitment of NK cells at the site of vaccination.